MEASUREMENT OF DISSOLVED INORGANIC NUTRIENT IN EUPHOTIC ZONE THE BANTEN BAY - Alianto Alianto; Enan M. Adiwilaga; Ario Damar; Enang Harris (Universitas Gadjah Mada, 2009)
At a few this last years, measurement concentration of dissolved inorganic nutrient is has rapidlyed grow by using various methods. But method anything applied must based on at formation of indicator end of measurement amonia, nitrite, nitrate, orthophosphate and silicate. At measurement of amonia its indicator is formation of blue indophenol, nitrite formation of pink azo, nitrate formation of yellow colored solution, orthophosphate formation of blue molybdenum, and silicate based on formation of yellows silicomolibdate. The intensity of color that is highly dependent on the concentration of each element. Measurement of amonia blue indophenol intensity perfected concentration in the range 0.206-0.396 mg/L. Measurement nitrite the formation of a pink azo easy imperfect because its low concentration. Intensity measurements nitrate solution yellow perfect concentration in the range 0.128-0.989 mg/L. Measurement of imperfect blue molybdenum intensity orthophosphate because its low concentration. While measuring the formation silicate of yellow silicomolibdate perfect concentration on the range 10.573-26.470 mg/L. As a whole from result of measurement is obtained chemical composition of dissolved inorganic nutrient in euphotic zone the Banten bay is more predominated by silicate 97.27%, nitrate 1.84%, amonia 0.49%, orthophosphate 0.20%, and nitrite 0.18%.